Epigenetic status of LINE-1 predicts clinical outcome in early-stage rectal cancer - Benard, A (Nature Publishing Group, 2013)
BACKGROUND: We evaluated the clinical prognostic value of methylation of two non-coding repeat sequences, long interspersed element 1 (LINE-1) and Alu, in rectal tumour tissues. In addition to DNA methylation, expression of histone modifications H3K27me3 and H3K9Ac was studied in this patient cohort. METHODS: LINE-1 and Alu methylation were assessed in DNA extracted from formalin-fixed paraffin-embedded tissues. A pilot (30 tumour and 25 normal tissues) and validation study (189 tumour and 53 normal tissues) were performed. Histone modifications H3K27me3 and H3K9Ac were immunohistochemically stained on tissue microarrays of the study cohort. RESULTS: In early-stage rectal cancer (stage I-II), hypomethylation of LINE-1 was an independent clinical prognostic factor, showing shorter patient survival (P=0.014; HR: 4.6) and a higher chance of tumour recurrence (P=0.001; HR: 9.6). Alu methylation did not show any significant correlation with clinical parameters, suggesting an active role of LINE-1 in tumour development. Expression of H3K27me3 (silencing gene expression) and H3K9Ac (activating gene expression) in relation to methylation status of LINE-1 and Alu supported this specific role of LINE-1 methylation. CONCLUSION: The epigenetic status of LINE-1, but not of Alu, is prognostic in rectal cancer, indicating an active role for LINE-1 in determining clinical outcome.